Validation of analytical methodology for quantification of cefazolin sodium pharmaceutical dosage form by high performance liquid chromatography to be applied for quality control in pharmaceutical industry - Pedroso, Tahisa Marcela [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Universidade de São Paulo (USP), Conjunto Quimicas, 2014)
A reversed-phase high performance liquid chromatography method was validated for the determination of cefazolin sodium in lyophilized powder for solution for injection to be applied for quality control in pharmaceutical industry. The liquid chromatography method was conducted on a Zorbax Eclipse Plus C-18 column (250 Chi 4.6 mm, 5 mu m), maintained at room temperature. The mobile phase consisted of purified water: acetonitrile (60: 40 v/v), adjusted to pH 8 with triethylamine. The flow rate was of 0.5 mL min(-1) and effluents were monitored at 270 nm. The retention time for cefazolin sodium was 3.6 min. The method proved to be linear (r(2)= 0.9999) over the concentration range of 30-80 mu g mL(-1). The selectivity of the method was proven through degradation studies. The method demonstrated satisfactory results for precision, accuracy, limits of detection and quantitation. The robustness of this method was evaluated using the Plackett-Burman fractional factorial experimental design with a matrix of 15 experiments and the statistical treatment proposed by Youden and Steiner. Finally, the proposed method could be also an advantageous option for the analysis of cefazolin sodium, contributing to improve the quality control and to assure the therapeutic efficacy.
Keywords: Cefazolin sodium/determination; High performance liquid chromatography/reverse-phase/quantitative analysis Pharmaceutical industry/quality control; Cefalosporine/quality control; Medicines/quality control